2021
DOI: 10.1530/joe-21-0129
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal androgen excess impairs beta-cell function by decreased sirtuin 3 expression

Abstract: Prenatal androgen exposure induces metabolic disorders in female offspring. However, the long-term effect of maternal testosterone excess on glucose metabolism, especially on pancreatic beta cell function, is rarely investigated. Our current study mainly focused on the effects of prenatal testosterone exposure on glucose metabolism and pancreatic beta cell function in aged female offspring. By using maternal mice and their female offspring as animal models, we found that prenatal androgen treatment induced obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Until recently, little was known about the role of Sirt3 in pancreatic development. A recent study showed that prenatal testosterone exposure impaired insulin secretion in elderly female offspring via suppressing Sirt3 [ 48 ]. These finding implies an underlying association between Sirt3 and β cell function during the embryonic period.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, little was known about the role of Sirt3 in pancreatic development. A recent study showed that prenatal testosterone exposure impaired insulin secretion in elderly female offspring via suppressing Sirt3 [ 48 ]. These finding implies an underlying association between Sirt3 and β cell function during the embryonic period.…”
Section: Discussionmentioning
confidence: 99%